IN VITRO ANTIOXIDANT CAPACITY, PHENOLIC, ASCORBIC ACID AND LYCOPENE CONTENT OF GUAVA (Psidium guajava L.) JUICES AND NECTARS - BRITO, CARLOS ALEXANDRE KOGUISHI DE; SIQUEIRA, PRISCILA BECKER; SOUZA, JANE CRISTINA DE; BOLINI, HELENA MARIA ANDRÉ (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2009)
capacity in vitro of three different brands of guava nectars and juices, through free radicals scavenging methods, 1,1-diphenyl-2-picrylhydrazine (DPPH) and 2,2'-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid (ABTS.+), and its correlation with the total polyphenolic content, total lycopene and ascorbic acid. Brands revealed statistical differences (p£ 0.05) in antioxidant capacity, ranging from 1.9 to 7.7 molTE/mL. Antioxidant capacity presented positive correlation for ascorbic acid content and polyphenolic compounds, being relatively low for the lycopene. Different process can influence the content of these compounds as well as interfere in their antioxidant capacity. The control of the production process is important to add value to guava products and fulfill the new tendency of the market.